Teacher Competencies in the Era of the Industrial Revolution 4.0: Transformation of Roles, Digital Skills, and Challenges of 21st-Century Education - Muhammad Ash'aril Fajri; Jumidi Eka Pratama; Abdurrahmansyah Abdurrahmansyah (Peneliti.net, 2026)
The Industrial Revolution 4.0 era has brought major disruption, changing the educational landscape through the integration of digital technologies such as Artificial Intelligence (AI) and the Internet of Things (IoT). These changes demand a fundamental transformation of the teacher's role, from a mere deliverer of material to a dynamic learning facilitator. This study aims to analyze the transformation of the teacher's role, the mastery of digital skills, as well as the challenges and strategies in facing 21st-century education. The research method used is a literature study (library research) by analyzing various relevant scientific sources. The results show that teachers in the digital era must master Technological Pedagogical Content Knowledge (TPACK), data literacy, and social-emotional learning (SEL) skills to create student-centered learning. The main challenges identified include technological infrastructure gaps and the need for continuous training. As a strengthening strategy, higher education institutions play a central role in shaping the character and work ethic of future educators, while teachers must adopt a lifelong learning mindset. The conclusion of this article emphasizes that the success of educational transformation depends on the synergy between technological sophistication and the cultivation of strong character values.